Public Services Quality at The Land Office of Lubuklinggau as an Integrity Zone Development Area - Putra Dempo, Agung Anugra; Firdaus; Hidayat, Rahmat (PERSPEKTIF, 2025)
This study aims to analyze the quality of public services at the Lubuklinggau City Land Office which has implemented the development of integrity zones and the implementation of electronic services. This study uses a qualitative method with a descriptive approach. The study results show that the quality of public services at the Lubuklinggau City Land Office is assessed in terms of tangible aspects, reliability, responsiveness, assurance, and empathy as good but still needs improvement. Several factors that support service quality are electronic service applications provided by the central government, the use of technology in services, clear procedures and SOPs, supportive policies and regulations, and evaluation and supervision. In addition, factors that inhibit service quality are human resources, community response to accommodation and transportation costs, and community response to electronic certificates. Furthermore, factors that also inhibit are changes in services to electronic certificates, imperfect electronic service applications, and limited facilities and infrastructure. Therefore, it is necessary to improve regulations, increase outreach, consummation at the applications, and fulfill facilities and infrastructure to maximize service quality.